Distribución radicular, absorción de nutrientes y erosión edáfica en sistemas de cultivos y forrajes en laderas del Cauca, Colombia - Ricaurte Oyola, José Jaumer; Zhiping Qui; Filipe, D; Rao, Idupulapati M.; Amézquita Collazos, Edgar (2000)
The extent of soil degradation in Andean hillsides limits plant productivity and therefoe affects sustainable human development in the region. The traditional systems in these agroecosystems indude agricultural and livestock exploitations where the crop and forage plants are important elements. Rooting characteristics of crop and forage components of production systems in hillsides could have important effects on nutrient acquisition and plant growth as well as reducing soil loss. An experiment was established in 1994 in Cauca, Colombia, to generate principles based on rooting strategies for improving crop-livestock production while conserving the natural resource base. Soils at the site are medium to fine textured Oxic Dystropepts derived from volcanic-ash deposits. Treatments (crop and forage systems) were established on steep slopes (43-46%). Six treatments, cassava monocrop, cassava + cover legumes intercrop, elephant grass (Pennisetum purpureum) pasture, imperial grass (Axonopus scoparius) pasture, introduced legume-based pasture and naturalized pasture were selected to determine differences in dry matter partitioning, leaf area index, nutrient composition, root distribution, nutrient acquisition and soil loss. Root biomass of the cassava + cover legumes intercrop was 44% greater than that of the cassava monocrop. The presence of cover legumes not only reduced soil erosion but also improved potassium acquisition by cassava. Among the two pastures, elephant grass pasture had greater root biomass (9.3 t/ha) than the imperial grass (4.2 t/ha). The greater root length density (per unit soil volume) of the former contributed to superior acquisition of nitrogen, phosphorus, potassium and calcium from soil. In addition, the abundance of very fine roots in elephant grass pastures in the topsoil reduced the loss of soil from the steep slopes. Naturalized pasture (Melinis minutiflora) developed a finer root system than the introduced legume-based pasture (Brachiaria humidicola + Arachis pintoi + Centrosema macrocarpum + Stylosanthes guianensis) but recycling of potassium and calcium via roots was greater with the introduced legume-based pasture than that of the naturalized pasture. These results indicate that (i) the presence of cover legumes can improve potassium acquisition by cassava and potassium and calcium cycling by introduced pastures; and (ii) elephant grass can be used as an effective grass barrier to reduce soil erosion in Andean hillsides.